2006
DOI: 10.1111/j.1398-9995.2006.01228.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in nonallergic nasal polyps associated with bronchial hyperresponsiveness1

Abstract: These results suggest an important role for oxidative stress in the pathophysiology of NP and a causal relation between oxidative stress and inflammatory cells, especially the eosinophils. Free radical levels in polyp-tissues associated with NP severity and with BHR/asthma phenotype in nonallergic NP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…Dagli et al [17] investigated the role of free radicals and antioxidants in nasal polyps and suggested that the levels of antioxidants were decreased and the levels of oxidants were increased. Cheng et al [18] demonstrated that the mean level of tissue chemiluminescence in nasal polyps was significantly higher than control specimens, and the expression of superoxide dismutase 1 and 3 was higher in nasal polyp tissues. However, these studies focused on mucosal damage by ROS, while we focused on the role of ROS in signal mediators in TGF-β1-induced NPDFs.…”
Section: Discussionmentioning
confidence: 99%
“…Dagli et al [17] investigated the role of free radicals and antioxidants in nasal polyps and suggested that the levels of antioxidants were decreased and the levels of oxidants were increased. Cheng et al [18] demonstrated that the mean level of tissue chemiluminescence in nasal polyps was significantly higher than control specimens, and the expression of superoxide dismutase 1 and 3 was higher in nasal polyp tissues. However, these studies focused on mucosal damage by ROS, while we focused on the role of ROS in signal mediators in TGF-β1-induced NPDFs.…”
Section: Discussionmentioning
confidence: 99%
“…Second, obesity characterised by increased systemic inflammation has been associated with increased progression of BHR and asthma 31. Third, Cheng et al 50 found a gradient of free radical concentrations in nasal polyps, an inflammatory chronic disease frequently associated with BHR and asthma. Concentrations were lowest in cases with nasal polyps without BHR and asthma, intermediate in those with concurrent silent BHR and highest in cases of nasal polyps with concurrent BHR and asthma.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of malondialdehyde, one of the metabolites of free radical-mediated lipid peroxidation, were observed in nasal polyps [8,9]. Moreover, free radical levels in nasal polyps were associated with nasal polyp severity [10,11]. The overproduction of free radicals and decrements in the antioxidant system can both cause tissue injury.…”
Section: Introductionmentioning
confidence: 99%